Are left ventricular ejection fraction and left atrial diameter related to atrial fibrillation recurrence after catheter ablation?: A meta-analysis. Issue 20 (May 2018) - Jin, Xiao; Pan, Jianke; Wu, Huanlin; Xu, Danping
Abstract : Abstract: Atrial fibrillation (AF), the most common form of arrhythmia, is associated with the prevalence of many common cardiovascular and cerebrovascular diseases. Catheter ablation is considered the first-line therapy for AF; however, AF recurrence is very common after catheter ablation. Studies have been performed to analyze the factors associated with AF recurrence, but none have reached a consistent conclusion on whether left ventricular ejection fraction (LVEF) and left atrial diameter (LA diameter) affect AF recurrence after catheter ablation. The databases PubMed, Embase, and the Cochrane Library were used to search for relevant studies up to September 2017. RevMan 5.3.5 software provided by the Cochrane Collaboration Network was used to conduct this meta-analysis. Thirteen studies involving 2825 patients were included in this meta-analysis. Overall, the results revealed that elevated LA diameter values were significantly associated with AF recurrence in patients after catheter ablation (MD = 2.19, 95% CI: 1.63–2.75, P < .001), while baseline LVEF levels were not significantly positively associated with AF recurrence in patients after catheter ablation (MD = −0.91, 95% CI: −1.18 to 1.67, P = .14). Overall, elevated LA diameter may be associated with AF recurrence after catheter ablation; however, there was no direct relationship between LVEF values and AF recurrence after catheter ablation when baseline LVEF values are normal or mildly decreased. Besides, because of publication bias, further studies should be performed to explore the mechanisms underlying AF recurrence.